2007
DOI: 10.1103/physrevc.75.035809
|View full text |Cite
|
Sign up to set email alerts
|

Sub-barrier fusion of neutron-rich nuclei and its astrophysical consequences

Abstract: Near-barrier fusion of neutron-rich nuclei was studied within the semiempirical channel coupling model for intermediate neutron rearrangement and within the time-dependent three-body Schrödinger equation. The possibility of neutron transfer with positive Q values considerably increases the barrier penetrability. A huge enhancement of deep sub-barrier fusion probability was found for light neutron-rich weakly bound nuclei (such as 6 He). This may be quite important for astrophysical primordial and supernova nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 46 publications
6
93
0
Order By: Relevance
“…4. The near barrier neutron transition with 0 Q > from the 1d 5/2 ( 18 O) state to the low-lied 1g 9/2 ( 58 Ni) state is, in a certain sense, an "energy lift" for the two interacting nuclei [1]. The total barrier penetration probability and the fusion cross section may increase due to a gain in the relative motion energy in this case.…”
Section: The Neutrons Rearrangement In the Centralmentioning
confidence: 94%
See 1 more Smart Citation
“…4. The near barrier neutron transition with 0 Q > from the 1d 5/2 ( 18 O) state to the low-lied 1g 9/2 ( 58 Ni) state is, in a certain sense, an "energy lift" for the two interacting nuclei [1]. The total barrier penetration probability and the fusion cross section may increase due to a gain in the relative motion energy in this case.…”
Section: The Neutrons Rearrangement In the Centralmentioning
confidence: 94%
“…The numerical solving of the time-dependent Schrödinger equation (TDSE) provides new possibilities for theoretical study of transfer reactions and the first capture stage of fusion reactions [1]. In this study the spin-orbital interaction [2], two-center states [3][4][5][6], the Pauli's exclusion principle [7] and the shell structure of deformed nuclei [8,9] were taken into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Coupling channel Results of calculations by formulas (2), (3), (14) with the proximity potential for the fusion cross section s and channel functions , , ( ) (Fig. 8) and coefficients a a of series expansion of the time-dependent valence neutron wave function ( , ) t Y r [9,12,13] for the head-on nucleus-nucleus collision occurs for the coupling strength value 15 t F = . In the vicinity of the Coulomb barrier the transition between two-center energy levels from the 1d 5/2 (O) to 1g 9/2 (Ni) with ( ) …”
Section: The Neutron Transfer Channels Couplingmentioning
confidence: 99%
“…Calculations performed within the microscopic timedependent Schrödinger equations [18] have clearly demonstrated that at low collision energies of heavy ions nucleons do not "suddenly jump" from one nucleus to another. Instead of that, the wave functions of valence nucleons occupy the two-center molecular states spreading gradually over volumes of both nuclei (see Fig.…”
Section: The Modelmentioning
confidence: 99%